ANALISISCAR/KPMM, LDRDAN NPL SERTA PENGARUHNYA TERHADAP ROAPADA PT BPR SINDANG BINAHARTA PERIODE 2011-2015 - Herman Paleni (Jurnal Media Ekonomi (JURMEK), 2016)
This research was conducted to determine the Capital Adequacy Ratio (CAR), the Loan to Deposit Ratio (LDR) and Non-Performing Loan (NPL) and the effect on Return on Assets (ROA) at PT BPR Sindang Binaharta Lubuklinggau for the period 2011 to 2015 This type of research is associative research. The data sources used are secondary data with time series methods originating from financial statements in the form of balance sheets, profit and loss and quality of productive assets between 2011 and 2015. Data collection is done using the documentation method. The analysis technique used is multiple regression and is equipped with the classic assumption of normality to get a regression model. The hypothesis is tested using simultaneous and partial statistical tests at a significance level of 5%. Based on the data used in this study, the data are normally distributed, so that they fulfill the requirements of multiple regression models. The results of the study showed that using a 0.05 level of significance, namely CAR / KPMM, LDR and NPL simultaneously had a positive and significant effect on ROA. Partially CAR / KPMM has a negative and significant effect on ROA, LDR has a negative and significant effect on ROA while NPL has a positive and significant effect on ROA.